A Review of Analysis of Partial Discharge Measurements using Coupling Capacitor in Rotating Machine - Ahmad Syukri Abd Rahman; Mohamad Nur Khairul Hafizi Rohani; Nur Dini Athirah Gazata; Afifah Shuhada Rosmi; Ayob Nazmi Nanyan; Aiman Ismail Mohamed Jamil; Mohd Helmy Halim Abdul Majid; Normiza Masturina Samsuddin (Iranian Journal of Electrical and Electronic Engineering)
Partial discharge (PD) is a critical phenomenon in electrical systems, particularly in high-voltage (HV) equipment like transformers, cables, switchgear, and rotating machines. In rotating machines such as generators and motors, PD is a significant concern as it leads to insulation degradation, potentially resulting in catastrophic failure. Effective and reliable diagnostic techniques are essential for detecting and analyzing PD to ensure the operational safety and longevity of such equipment. Various PD detection methods have been developed, including coupling capacitor (CC), high-frequency current transformer (HFCT), and ultra-high frequency (UHF) techniques, each offering unique advantages in assessing the condition of HV electrical systems. Among these, coupling capacitors have gained significant attention due to their ability to improve the accuracy, sensitivity, and efficiency of PD detection in rotating machines. This study focuses on the advancements in coupling capacitor-based techniques and their critical role in enhancing PD diagnostics for monitoring and maintaining high-voltage rotating machinery.